2015
DOI: 10.1177/0891988715606230
|View full text |Cite|
|
Sign up to set email alerts
|

Cortical Amyloid β Deposition and Current Depressive Symptoms in Alzheimer Disease and Mild Cognitive Impairment

Abstract: Depressive symptoms are frequently seen in patients with dementia and mild cognitive impairment (MCI). Evidence suggests that there may be a link between current depressive symptoms and Alzheimer disease (AD)-associated pathological changes, such as an increase in cortical amyloid-β (Aβ). However, limited in vivo studies have explored the relationship between current depressive symptoms and cortical Aβ in patients with MCI and AD. Our study, using a large sample of 455 patients with MCI and 153 patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 60 publications
2
23
0
1
Order By: Relevance
“…This is highlighted by the study’s secondary analyses, where there was no difference in amyloid binding observed between early-onset and late-onset depressed subjects (1). Supporting these findings, some previous studies in both cognitively impaired and cognitively intact older adults have similarly failed to associate amyloid burden with depressive symptoms (7; 8). Even more compellingly, a large longitudinal neuropathological study found that the occurrence of depression was not related to a specific underlying neuropathology, and the effect of depressive symptoms on cognitive decline was unrelated to and independent of underlying neuropathology (9).…”
supporting
confidence: 62%
“…This is highlighted by the study’s secondary analyses, where there was no difference in amyloid binding observed between early-onset and late-onset depressed subjects (1). Supporting these findings, some previous studies in both cognitively impaired and cognitively intact older adults have similarly failed to associate amyloid burden with depressive symptoms (7; 8). Even more compellingly, a large longitudinal neuropathological study found that the occurrence of depression was not related to a specific underlying neuropathology, and the effect of depressive symptoms on cognitive decline was unrelated to and independent of underlying neuropathology (9).…”
supporting
confidence: 62%
“…Lastly, cortical Aβ accumulation is an early-occurring pathological change, whose rate of deposition slows down over the course of the disease in elderly individuals (40). As a result, we may not have observed drastic changes in cortical Aβ levels over the 2 years of follow-up in both the CON+BZD and CON-BZD groups.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, the amount of deposited amyloid correlated with the rate of progression in depressed individuals (Brendel et al , 2015). In contrast to studies that reported a relationship between neuropsychiatric symptoms and amyloid deposition, a study among patients with MCI and AD failed to detect an association between cortical amyloid deposition and depressive symptoms (Chung et al , 2016). Our findings may be pertinent to the recently reported construct of Mild Behavioral Impairment (MBI) which is defined as a change in behavior or personality in non-demented persons aged 50 years and older (Ismail et al , 2016).…”
Section: Discussionmentioning
confidence: 95%